Sidedness Matters: Surrogate Biomarkers Prognosticate Colorectal Cancer upon Anatomic Location. (12th February 2019) - Ben‐Aharon, Irit; Goshen‐Lago, Tal; Sternschuss, Michal; Morgenstern, Sara; Geva, Ravit; Beny, Alexander; Dror, Ygael; Steiner, Mariana; Hubert, Ayala; Idelevich, Efraim; Shulman, Katerina; Mishaeli, Moshe; et al.
Abstract: Background: Anatomic location of primary tumors across the colon correlate with survival in the metastatic setting, whereas left‐sided tumors may exhibit superior survival compared with right‐sided tumors. The Oncotype Recurrence Score (RS) assay is a clinically validated predictor of recurrence risk in patients with stage II colorectal cancer (CRC). Previous studies had indicated that without adjuvant chemotherapy, CDX2‐negative stage II CRC tumors are associated with a lower rate of disease‐free survival than CDX2‐positive stage II CRC tumors. We aimed to evaluate whether these two validated prognostic biomarkers may correlate with primary tumor location, and whether tumor location may reflect differential prognosis in stage II CRC. Materials and Methods: We retrospectively analyzed patients with T3 mismatch repair‐proficient (MMR‐P) stage II CRC for whom RS assay was performed. Pathological report was reviewed for exact primary tumor location and CDX2 immunostaining. RS and CDX2 expression were correlated with primary tumor location. Results: The analysis included 1, 147 patients with MMR‐P stage II CRC (median age 69 years [range 29–93]). Tumor distribution across the colon was as follows: 46% ( n = 551) were right‐sided and 54% ( n = 596) were left‐sided. RS was higher in right‐sided tumors ( p = .01). The RS results gradually decreased across the colon (cecum, highest score; sigmoid, lowest score; p = .04). Right‐sided tumors exhibited more CDX2‐negative tumors ( p = .07). Conclusion: Our study indicates that right‐sided colorectal tumors may display worse prognosis compared with left‐sided tumors in MMR‐P stage II CRC. Primary tumor location may serve as a prognostic factor that should be taken into account for recurrence risk assessment and consideration of adjuvant treatment. Abstract : This article evaluates prognostic biomarkers with a focus on primary tumor location in stage II colorectal cancer.